A Study on Domestic Energy Situation at different Altitudes of Himachal Pradesh - Mani, Indra; Kumar, Pradeep; Panwar, J S (Journal of Agricultural Engineering, 2007)
This paper presents energy availability and consumption pattern at three different altitudes in rural areas of Western Himalayas in Himachal Pradesh, India and explores the possibility of implementing efficient conversion of locally available resources of energy like fuel wood, agricultural residues and cow dung to assure proper energy supply. Energy data was collected from 90 households on different household activities and their source of energy. Among the conventional energy sources, the highest contribution was of electrical energy, which was to the tune 7% of the total energy consumption. The share of non-commercial energy sources accounted for 91% of the total available domestic energy in all the three altitudes. Out of total domestic energy, fuel wood contributed 79-87 per cent, 70% of which was used for cooking. Space and water heating consumed major portion of fuel wood in all the three altitudes. Although, the agricultural residues recorded second highest share in non commercial energy availability at all the three altitudes but in sharp contrast, to fuel wood their use was just 5 per cent in low altitude, and almost negligible in other two altitudes. The efficient energy conversion technology like Modified Stoves (chullas) for cooking could save a highest of 99.8 MJ/day/household and use of electric kettle ( Bijuli Dekchi) and Back Boiler for water heating could save a highest of 80 MJ/day/household of fuel wood energy in high hills. Proper energy management could help ameliorating energy problem in hilly areas and may also save forest by reducing firewood consumption.